The Influence of Digital Marketing, Halal Awareness, and Brand Experience on Interest in Buying Safi Skincare among Syiah Kuala University Students - Putri, Amanda Devina; Sitepu, Novi Indriyani (International Journal of Kita Kreatif, 2025)
This research aims to analyze the influence of digital marketing, halal awareness, and brand experience on interest in buying Safi skincare among Syiah Kuala University students. This research uses a quantitative approach. The data used is primary data obtained from distributing questionnaires to 100 respondents. Researchers determined respondents using non-probability sampling techniques with the Slovin formula and analyzed using multiple linear regression analysis. The results of this research show that digital marketing variables have a negative and significant effect on purchasing interest. Halal awareness and brand experience has a positive and significant effect on purchasing interest. Simultaneous test results show that the variables digital marketing, halal awareness, brand experience have a significant effect on interest in buying Safi skincare among Syiah Kuala University students.Keyword: Digital Marketing, Halal Awareness,Brand Experience, Purchase Interest